Pertanggungjawaban Pidana Anak Sebagai Pelaku Tindak Pidana Pengeroyokan Yang Menyebabkan Kematian (Studi Putusan No. xx/Pid.Sus-Anak/2025/PN Tjk) - Justicia, Ryan; Manaf, Idham (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2026)
Group assault resulting in death constitutes a grave criminal offense that directly violates the fundamental right to life. The legal complexity of such cases becomes more significant when the perpetrators are juveniles, as the criminal justice system must balance the objectives of punishment, justice for victims, and the protection of the best interests of the child. Juveniles, as individuals who are still in the process of physical, psychological, and social development, require a distinct legal approach compared to adult offenders. This study aims to examine the legal framework governing juvenile criminal liability in cases of group assault resulting in death and to analyze the considerations taken by judges in imposing criminal sanctions, with specific reference to Decision Number xx/Pid.Sus-Anak/2025/PN Tjk. This research employs a normative juridical approach supported by an empirical approach. The normative approach is conducted through a comprehensive analysis of statutory regulations, particularly Law Number 11 of 2012 concerning the Juvenile Criminal Justice System, the Indonesian Criminal Code, relevant legal doctrines, and judicial precedents. Meanwhile, the empirical approach is carried out through interviews with law enforcement officials to obtain factual insights into the practical application of juvenile criminal law. The collected data are analyzed qualitatively to assess the consistency between legal norms and judicial practice.The findings reveal  that juveniles may be held criminally responsible for acts of group assault resulting in death, provided that the elements of the offense and the requirements of criminal liability are fulfilled. However, the imposition of criminal sanctions must prioritize the principles of child protection, proportionality, and rehabilitation, as mandated by juvenile justice legislation. Judicial considerations in such cases extend beyond juridical elements and include non-juridical factors such as the age of the juvenile, psychological maturity, social and family background, level of participation in the offense, expressions of remorse, and prospects for rehabilitation. Ultimately, judicial decisions are expected to reflect a balanced form of justice that safeguards the rights and future of the child while simultaneously addressing the sense of justice for victims and the wider community.